Demulsification of water-in-crude oil emulsions via microwave heating technology - Rajanderan, R Sothilakshmi (2010)
The traditional ways of breaking emulsions using heat and chemicals are disadvantageous from both economic and environmental perspectives. In this study, an alternative and cost effective technology for high frequency energy separation of oil emulsions has developed. The potentials of microwave technology in demulsification of water-in-crude oil emulsions are investigated. After exposing the emulsion to the microwave electromagnetic (EM) field, molecular rotation, and ionic conduction due to the penetration of EM into the emulsion are responsible for the internal heating. In this study, microwave demulsification was applied in a 50-50 %, 30-70 % and 10-90 % water-in-oil emulsions with microwave exposure time varied from 20-200 sec. The temperature rise at a given location was almost horizontal (linear). The average rates of temperature increase of 50-50 %, 30-70 % and 10-90 % water-in-oil emulsion are 1.042, 0.582 and 0.218 oC/sec, respectively. The rate of temperature increase of emulsions decreased at higher temperature due to decreasing dielectric loss of water. Viscosity increases with amount of surfactant used, whereas, viscosity and shear stress decreases as temperature and rpm increased.